STRESS REMAGNETIZATION IN PYRRHOTITE-CALCITE SYNTHETIC AGGREGATES - Robion Ph.; Borradaile G.J. (My University, 2001)
Stress-induced remagnetization has been applied to multidomain pyrrhotite-calcite synthetic aggregates in a triaxial rig. Experimental deformation used 150 MPa confining pressure, a constant strain rate of 10-5 s-1 and applied differential stresses of up to 70 MPa. New components of magnetization, parallel to the direction of the pressure vessel field, were added to the pre-deformational magnetization. The intensity of remagnetization (M' - M0) increases with the intensity of the applied differential stress and affects the coercivity fraction below 15 mT. Bulk shortening is less than 8 per cent, thus grain rotation cannot explain selective remagnetization of the low-coercivity fraction. Remagnetization is thus attributed to deformational viscous remanent magnetization (DVRM). It is observed that high-coercivity (> 15 mT) grains do not remagnetize. There is, however, slight progressive rotation of pre-deformational magnetization with increasing strain up to 8 per cent of bulk shortening. The lack of piezoremanent magnetization in the high-coercivity range may be due to defects introduced in pyrrhotite during sample preparation. Experiments using synthetic pyrrhotite, expected to show low dislocation densities, would be necessary to test this effect.
Keywords: PYRRHOTITE; REMAGNETIZATION; STRAIN; STRESS; TRIAXIAL DEFORMATION